PENGGUNAAN STRATEGI PEMBELAJARAN AKTIF UNTUK MENINGKATKAN EFEKTIVITAS PEMBELAJARAN - Marlan Marlan; Syaiful Anwar (Manajer Pendididikan, 2021)
Abstract: This study aims to find a strategy for effective learning and teaching materials Efficient in reaction stoichiometry for students in SMAN 5 South Bengkulu by enabling students to learning. Strategies in the classroom action research was conducted in two cycles and in each cycle includes planning, implementation, observation and reflection. Meanwhile, to enable students in this study, researchers used a worksheet given to students in large groups and small groups. Which is the subject of the study of this class action is a class X IPA.1 SMAN 5 South Bengkulu being the object is learning the material stoichiometric chemical reactions on subjects that are taught in a way to enable students in small groups and large groups. From research conducted by examining the initial conditions of students as measured by means of a written test and the results of classroom action research with two cycles seen an increase results achieved by students in mastering the material stoichiometry given. Increasing mastery of this material from the first cycle of students can be increased by 28.5% from the initial conditions being on the conditions in the first cycle after the action on the second cycle increased by 39.36%. The results of this class action, the researchers recommend the policy maker or implementer of learning in this case the teachers to teach the learning material in small groups and with techniques to enable the students. Keywords :1. Active Learning.2. Effective Learning.3. reaction stoichiometry.